Pengembangan Flipbook Berorientasi Hots pada Materi Sistem Reproduksi untuk Peserta Didik Kelas XI SMA Negeri 1 Tegallalang - Ni Made Widiastuti; I Wayan Sukra Warpala; Ni Putu Sri Ratna Dewi (Jurnal Pendidikan Biologi Undiksha, 2022)
The purpose of this research is to know the design, feasibility, and practicality of a HOTS-oriented flipbook on the human reproductive system material for class XI students of SMA Negeri 1 Tegallalang. This research and development research uses the ADDIE development model. The tests carried out in this study consisted of a feasibility test and a practicality test. The feasibility test is carried out by one material expert and one media expert. The practicality test in this study was carried out by students of class XI as many as 3 students for individual trials and 12 students for group trials. The data collection technique was carried out by filling out the instruments in the questionnaire. The instruments used are online preliminary study questionnaires, feasibility test questionnaires and practicality test questionnaires. Data analysis was carried out descriptively to determine the level of feasibility and practicality of the flipbook. The results of this study are 1) the design of a HOTS-based flipbook consisting of an introduction, core material and closing. 2) the feasibility test shows a percentage of 89.99% by material experts and 90.52 by media experts with a very decent category, and 3) the practicality test is obtained from student responses of 92.85% from individual tests and 93.92% from a small group test with a very practical category. The unique of the flipbook is that it is structured HOTS-oriented with features that adapt to different student learning styles. Based on the research, the conclusion obtained is that the HOTS-oriented flipbook on the material of the human reproductive system is stated to be very feasible and very practical to use as an alternative media in learning activities. Keywords: Flipbook, HOTS, Human Reproductive System.